PhD-prepared nurses leading their careers - van Dongen, Lisa (fi=Turun yliopisto|en=University of Turku|, 2025)
The aim of this study was to describe the careers of PhD-prepared nurses and analyse leadership practices in the careers as well as support sources for the careers. The first phase comprised the analytics of leadership practices in the careers of PhD-prepared nurses using an interview study with 12 PhD-prepared nurses. Evaluation of a leadership and mentoring program was used to understand leadership practices in the careers and to determine if the program was a support sources for careers. A pre-post-test program evaluation was conducted among 30 participants using questionnaires. Also, focus group interviews were conducted among a convenience sample of 21 participants. The second phase aimed at the analytics of the careers and factors related to the careers including leadership practices in the careers and support sources for careers. An integrative literature review with 22 papers provided a theoretical overview and a cross-sectional survey study with 1308 PhD-prepared nurses was used to gain insight into the current careers and factors related to careers. The results demonstrate PhD-prepared nurses working in a wide range of positions across different areas of nursing, with most working in positions with research and teaching responsibilities at institutions of higher education. Leadership practices were demonstrated with the aim to advance their careers and included taking initiative for planning and progressing careers. Careers and leadership practices can be supported through programs such as the Nurse-Lead leadership and mentoring program. Factors related to careers that can be influenced by individuals were intrinsic motivation, work-life balance, encountered workplace behaviours, and development of professional and leadership competencies. Support sources for careers included support from family and friends, collegial support, mentoring, educational programs, and organizational infrastructures for careers. The conclusion is that there is large variance in the careers, PhD-prepared nurses demonstrate leadership to advance careers, and there are various support sources for careers. This study provides recommendations for PhD-prepared nurses to lead their careers and recommendations for leaders of professional organizations to develop support sources. Future research is recommended to systematically monitor careers of PhD-prepared nurses and factors related to careers using representative samples

Tohtorintutkinnon suorittaneet sairaanhoitajat johtavat uraansa Tämän tutkimuksen tavoitteena oli kuvata tohtorikoulutettujen sairaanhoitajien uria ja analysoida johtamiskäytäntöjä uralla sekä erilaisia tukirakenteita tohtorikoulutettujen sairaanhoitajien uralla. Tutkimuksen ensimmäisessä vaiheessa analysoitiin tohtorikoulutettujen sairaanhoitajien uran johtamiskäytäntöjä haastattelututkimuksen avulla, johon osallistui 12 tohtorikoulutettua sairaanhoitajaa. Tohtorikoulutetuille sairaanhoitajille ja alan väitöskirjatutkijoille suunnatun johtamis- ja mentorointiohjelman avulla analysoitiin uriin liittyviä johtamiskäytäntöjä ja arvioitiin ohjelmaa uran johtamisen tukirakenteena ennen-jälkeen asetelmassa kyselylomakkein 30 osallistujalle, ja teemahaastatteluin 21 osallistujasta koostuvalle harkinnan-varaiselle otokselle. Tutkimuksen toisessa vaiheessa keskityttiin urien analyysiin ja uriin liittyviin tekijöihin, mukaan lukien johtamiskäytännöt ja uran tukilähteet ja -rakenteet. Integroitu kirjallisuuskatsaus (n= 22 artikkelia) tuotti teoreettisen yleis-katsauksen, ja poikkileikkaustutkimus 1308 tohtorikoulutetun sairaanhoitajan maailmanlaajuisessa aineistossa syvensi ymmärrystä urista ja niihin liittyvistä tekijöistä. Tohtorikoulutettujen sairaanhoitajien urissa on suurta vaihtelua, sillä he työskentelevät monilla eri hoitotyön alueilla erilaisissa tehtävissä. Suurin osa työskenteli tutkimus- ja opetustehtävissä korkeakouluissa. Tohtorikoulutetut sairaanhoitajat hyödynsivät johtamiskäytäntöjä edistääkseen uraansa. Johtamiskäytännöt sisälsivät aloitteellisuutta uran suunnittelussa ja kehittämisessä. Tohtori-koulutettujen sairaanhoitajien uria ja johtamiskompetensseja voidaan tukea ohjelmien, kuten Nurse-Lead-johtamis- ja mentorointiohjelman, avulla. Urakehitykseen vaikuttavia tekijöitä, joita voidaan edistää johtamiskäytännöillä, olivat sisäinen motivaatio, työ- ja yksityiselämän tasapaino, työpaikalla kohdatut käyttäytymismallit sekä ammatillisten ja johtamisosaamisen kehittäminen. Urakehitykselle suotuisiksi lähteiksi kuvattiin kollegiaalinen ja epävirallinen tuki, yhteistyö, mentorointi, koulutusohjelmat ja organisatoriset rakenteet. Johtopäätöksenä on, että työurien välillä on suurta vaihtelua, tohtoriksi valmistuneilla sairaanhoitajilla on johtamiskäytäntöjä työurien edistämiseksi ja että työurien tukemiseksi on erilaisia tukilähteitä. Kehittämisehdotukset kohdistuvat oman uran johtajuuden ja organisaatioiden uria tukevien rakenteiden edistämiseen. Jatkossa olisi tärkeää kehittää järjestelmällinen tohtorikoulutettujen sairaanhoitajien urien ja niihin liittyvien tekijöiden seurantajärjestelmä, ja jatkaa globaalia tarkastelua.